2022
DOI: 10.1021/acsapm.2c01032
|View full text |Cite
|
Sign up to set email alerts
|

Porous Polymer Films with Tunable Pore Size and Morphology by Vapor Deposition

Abstract: The fabrication of porous polymer thin films with precise thickness and morphological control through conventional solvent-based techniques is challenging. Herein, we present a fabrication method for porous polymer thin films based on chemical vapor deposition that provides control over pore size, pore morphology, and film thickness. The porous films are prepared by co-depositing crystallizable porogen molecules with cross-linked poly(glycidyl methacrylate) (pGMA) thin films, which are synthesized by initiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…65 Recently, porous polymer films of cross-linked poly(glycidyl methacrylate) (pGMA) were prepared by vapor deposition, however the pores are not spherical or uniform in size and there is no evidences of any biological uses. 66 DOX loaded in chitosan hydrogel film reported, however the release was studied in acetic acid and within 1 h release reached to 70%, which was very first release. 67 Further, a biopolymers films for drug delivery and tissue engineering were prepared through the template synthesis or by 3D printing technology which is very costly.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…65 Recently, porous polymer films of cross-linked poly(glycidyl methacrylate) (pGMA) were prepared by vapor deposition, however the pores are not spherical or uniform in size and there is no evidences of any biological uses. 66 DOX loaded in chitosan hydrogel film reported, however the release was studied in acetic acid and within 1 h release reached to 70%, which was very first release. 67 Further, a biopolymers films for drug delivery and tissue engineering were prepared through the template synthesis or by 3D printing technology which is very costly.…”
Section: Discussionmentioning
confidence: 96%
“…A recent review on polymer films has been reported but all the porous polymer films were used for the separation technology 65 . Recently, porous polymer films of cross‐linked poly(glycidyl methacrylate) (pGMA) were prepared by vapor deposition, however the pores are not spherical or uniform in size and there is no evidences of any biological uses 66 . DOX loaded in chitosan hydrogel film reported, however the release was studied in acetic acid and within 1 h release reached to 70%, which was very first release 67 .…”
Section: Discussionmentioning
confidence: 99%
“…180 The relationship between pore morphology and porogen type was discussed. 181,182 The membrane morphologies of sphere agglomeration, unconnected sheets, and crater-like shapes were observed when a highly immiscible liquid porogen, a highly immiscible and crystallizable porogen, and the most miscible porogen were used, respectively. However, in previous reports, a porous structure could only be fabricated in a polymer membrane.…”
Section: Porosity and Gradientmentioning
confidence: 99%
“…Moreover, the development of optical coatings for flexible optics must consider the effect of processing steps on the substrates, which are often soft elastomeric materials with limited heat resistance. iCVD is a compelling processing technology given its ability to prepare films with exceptional control over thickness, composition, conformality, and spatial uniformity. Importantly, there is a limited heat transfer to the substrate, and substrates remain at low temperature throughout the iCVD process, enabling coatings to be prepared on temperature-sensitive substrates such as thermoplastic polyurethanes. , …”
Section: Introductionmentioning
confidence: 99%